CREATIVITY AS A WAY TO INTEGRATE ART INTO PRESCHOOL AND PRIMARY EDUCATION - Tiahur , Vasyl (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article reveals the role of creativity as a means of integrating art into the educational process of preschool and primary school. The article analyses pedagogical conditions that contribute to the development of creativity: facilitation, organization of creative environment, use of art materials, folk art, multimedia and inclusive approaches. The importance of art for the formation of imagination, aesthetic taste, emotional and spiritual sphere of the child through the use of art pedagogy is emphasized.